2022
DOI: 10.1073/pnas.2114971119
|View full text |Cite
|
Sign up to set email alerts
|

DNA-encoded library versus RNA-encoded library selection enables design of an oncogenic noncoding RNA inhibitor

Abstract: Significance Drug discovery generally investigates one target at a time, in sharp contrast to living organisms, which mold ligands and targets by evolution of highly complex molecular interaction networks. We recapitulate this modality of discovery by encoding drug structures in DNA, allowing the entire DNA-encoded library to interact with thousands of RNA fold targets, and then decoding both drug and target by sequencing. This information serves as a filter to identify human RNAs aberrantly produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 63 publications
0
33
0
Order By: Relevance
“…In particular, RNA-binding compounds on average have lower octanol–water partition coefficients (LogPs) than protein-binding compounds (ranges from two separate analyses: 0.16 ± 5 versus 2.0 ± 3.5 (ref. 109 ) and 1.02 versus 1.78 (ref. 283 ), respectively), greater topological polar surface areas (156 ± 118 versus 92 ± 144 Å 2 ) 109 , more hydrogen bond donors (5.2 ± 5 versus 2.0 ± 4) and acceptors (8.6 ± 6 versus 5.0 ± 6) 109 , and more heteroatom-containing aromatic rings (2.16 versus 1.25) 283 .…”
Section: Defining Rna Structures For Small-molecule Targetingmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, RNA-binding compounds on average have lower octanol–water partition coefficients (LogPs) than protein-binding compounds (ranges from two separate analyses: 0.16 ± 5 versus 2.0 ± 3.5 (ref. 109 ) and 1.02 versus 1.78 (ref. 283 ), respectively), greater topological polar surface areas (156 ± 118 versus 92 ± 144 Å 2 ) 109 , more hydrogen bond donors (5.2 ± 5 versus 2.0 ± 4) and acceptors (8.6 ± 6 versus 5.0 ± 6) 109 , and more heteroatom-containing aromatic rings (2.16 versus 1.25) 283 .…”
Section: Defining Rna Structures For Small-molecule Targetingmentioning
confidence: 99%
“… 109 ) and 1.02 versus 1.78 (ref. 283 ), respectively), greater topological polar surface areas (156 ± 118 versus 92 ± 144 Å 2 ) 109 , more hydrogen bond donors (5.2 ± 5 versus 2.0 ± 4) and acceptors (8.6 ± 6 versus 5.0 ± 6) 109 , and more heteroatom-containing aromatic rings (2.16 versus 1.25) 283 . An analysis by the Hargrove laboratory suggested that the shape of RNA binders is generally rod-like 283 .…”
Section: Defining Rna Structures For Small-molecule Targetingmentioning
confidence: 99%
See 2 more Smart Citations
“…1 By combining the merits of synthetic chemistry and DNA genetic barcoding, this technology generates a collection of numerous DNA-tagged compounds (from hundreds of millions to billions) via “split-and-pool” cycles, 2 which then are screened against therapeutic targets of interest (TOI). 3 The conjugated DNA tags that could be read out by the sequencing technique enable the identification of those high-affinity binders within a complex pool, thus rendering high throughput screening (HTS) at a lower cost and efficient time (Scheme 1a). 4 This competitive strategy featuring unique DNA barcodes, thereby, has been harnessed by both the pharmaceutical industry 5 and academia, 6 to facilitate the early stage of drug discovery, undoubtfully generating fruitful outcomes of clinical candidates represented by the RIPK1 inhibitor GSK2982772, 7 sEH inhibitor GSK2256294, 8 and autotaxin inhibitor X-165, 9 which were optimized from the corresponding DEL hits.…”
Section: Introductionmentioning
confidence: 99%